Diagnosing a solitary pulmonary nodule using multiple bronchoscopic guided technologies: A prospective randomized study - Bo, Liyan; Li, Congcong; Pan, Lei; Wang, Hongwu; Li, Shiyue; Li, Qiang; Bai, Chong; Zeng, Yiming; Nan, Yandong; Wang, Yan; Huang, Haidong; Zhou, Rui; et al. (Lung cancer (Amsterdam, Netherlands), 2019)
•Guided bronchoscopy was related to an increased diagnostic yield of SPNs.•VBN could not increase the diagnostic yield of peripheral lesions.•Application of VBN could shorten the bronchoscope arrival time. The rate of detection of pulmonary nodules on computed radiography (CR) is approximately 0.09–0.2%, so rapid identification of the nature of solitary pulmonary nodules (SPNs) with a likelihood of malignancy is a critical challenge in the early diagnosis of lung cancer. We conducted this study to compare the diagnostic yield and safety of endobronchial ultrasonography with a guide sheath (EBUS-GS), and the combination of EBUS-GS and virtual bronchoscopic navigation (VBN). This was a prospective, multicenter, multi-arm, randomized controlled trial involving a total of 1010 subjects. All the patients recruited underwent a chest CT scan which found SPNs that needed to be diagnosed. The subjects were randomly divided into one of three groups: a traditional, non-guided, bronchoscopy biopsy group (NGB group), an EBUS-GS guided bronchoscopy biopsy group (EBUS group), and a guided bronchoscopy biopsy group that combined EBUS-GS with VBN (combined group). The primary endpoint was to investigate the differences between the diagnostic yields of the three groups. There was no significant difference in the diagnostic yield between the EBUS group (72.3%) and the combined group (74.3%), but the diagnostic yield for the NGB group was 41.2%. The time required to reach biopsy position was significantly less in the combined group (7.96 ± 1.18 min in the combined group versus 11.92 ± 5.37 min in the EBUS group, p < 0.05). However, the bronchoscope operation time was the same in the EBUS-GS and combined groups. The diagnostic yield for peripheral pulmonary lesions (PPLs) >20 mm in diameter was significantly higher than for those <20 mm in diameter. The results of our study suggest that guided bronchoscopy could increase the diagnostic yield in the context of peripheral lesions. There was no significant difference in the diagnostic yield between the EBUS and combined groups, but use of EBUS-GS with VBN could significantly shorten the bronchoscope arrival time.